Synthesis of an Analytical System Prototype Using MQTT and AWS in the Industry 4.0 Context - Gaiduchek, Denis; Kryvoplias-Volodina, Liudmyla; Kostin, Volodymyr; Burova, Zinaida; Zaporozhets, Oleksandr (My University, 2025)
The designed system architecture and developed end-to-end prototype serves as a solid baseline for further system evolving and core functionality extension . The proposed approach is suitable for integration of the IIoT scenarios and applicable for variety of domains including packaging equipment capable to reduce operating costs at the development and testing stage, while maintaining the ability to scale system for industrial volumes. The proposed solution demonstrates practical implementation of Industry 4.0 principles in the field of packaging equipment, contributes to increasing production efficiency, and also creates a basis for the implementation of adapt ive mechanisms, preventive maintenance, and advanced real-time analytics.
Keywords: кафедра мехатроніки та пакувальної техніки; аналітична система (пакування); MQTT; Modbus; AWS IoT Core; Industry 4.0. Node-RED; analytical system (packaging)